Analisis Permasalahan antara Mahasiswa Fakultas Ilmu Keolahragaan dan Fakultas Teknik UNIMED sebagai Akibat Kurangnya Kesadaran akan Nilai – Nilai Pancasila - Debora Saragih; Dzurriyati Ayuni Aceh; Suryana Daulay; Ida Pakpahan; Yordan Sihotang; Rihandi Marpaung; Jernih Siahaan; Melda Sihotang; Tasya Pangaribuan; Sri Ayuni (International Forum of Researchers and Lecturers, 2024)
This research aims to investigate in depth the conflict between students from the Faculty of Engineering (FT) and the Faculty of Sports Science (FIK) at a university which started with a parking incident in the auditorium area. The method used in this research is a qualitative method. In-depth and semi-structured interviews were conducted using open-ended questions that included the chronology of events, the background of the conflict, the parties involved, resolution efforts, and the impacts caused. The results of the interviews revealed that the conflict started with a misunderstanding regarding parking which sparked initial arguments and fights, and escalated into further physical clashes with stones being thrown at each other, damage to facilities, and injuries to victims. Initial peace efforts failed, so a larger FIK crowd attacked the Engineering Faculty area. The conflict ended after the masses withdrew and the victims were evacuated to hospitals. Data analysis identifies patterns and perspectives from various parties, and formulates recommendations for more effective conflict management.